Identity, emotion, and feminist collective action - Hercus, Cheryl (Gender and Society, 1999)
This article explores the relationship between identity, emotion, and feminist collective action. Based on interview research, the analysis confirms the central importance of anger in collective action and its particular significance for feminist identity and activism. As an emotion thought deviant for women, the anger inherent in feminist collective action frames created problems for participants in terms of relationships with partners, friends, and work colleagues. Participants performed emotion work to deal with negative responses to their feminist identity, but this depleted emotional energy and created stress. Participation in movement events provided much-needed emotional support and an outlet for deviant emotions.
Keywords: 1900-1999; 1990-1999; australie; colère; discipline; militance; océanie; organisations féministes; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; étude qualitative

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Femmes du siècle - Institut de recherches et d'études féministes (FéminÉtudes, 1999)
Cette publication de 1999 porte sur l’histoire des féminismes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 1900-1999; 1990-1999; amériques; discipline; féminétudes; histoire; histoire des femmes*; histoire et politique; militance; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; thématiques

“EVERYTHING ABOUT US IS FEMINIST”: The Significance of Ideology in Organizational Change - Thomas, Jan E. (Gender & Society, 1999)
This study explores the role feminist ideology played in long-term structural changes in feminist organizations. The vehicle for this exploration was a comparative case study of 14 feminist women's health centers that were started in the 1970s and were still in existence in the early 1990s. Drawing on interviews and site visits, the author describes the early collectivist structures, highlights some of the crises these organizations faced, and describes three structural ideal types that emerged in the 1990s. The analysis suggests three ideological issues that directed structural change: the importance of maintaining a system for the equitable distribution of power, the importance of growth versus autonomy, and the importance of feminism as an organizational outcome or internal process.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem7000; justice sociale; militance; organisations féministes; pratiques féministes; périodes historiques; recherche participative; régions géographiques; sciences humaines; structures organisationnelles; thématiques; travail social; états-unis; étude de cas